Sandhill Milikweed, Asclepias humistrata - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Sandhill milkweed is scattered on backdunes, in sandhills, and often in disturbed areas, such as mowed roadsides. It has a range in Florida south to Lake Okeechobee and also occurs in coastal southeast states west to Louisiana and northeast to North Carolina. https://edis.ifas.ufl.edu/sg162